Descripción de las características de la memoria de trabajo en una persona de 21 años con Trastorno de Ansiedad Generalizada (TAG) a partir de un estudio de caso - Villa Suaza, Anlly Valentina; Toro Ramírez, Valentina; Vidal Ríos, Valeria (Universidad Cátolica Luis Amigó, 2020)
Generalized anxiety disorder is characterized by the presence of excessive worry and anxiety that are persistent and difficult to control about different aspects of life, such as work or school performance. Regarding the symptoms of this disorder, states of irritability, difficulties in concentrating and sleeping, nervousness, fatigue and even increased muscle tension or discomfort can be included. This disorder can be chronic and disabling for the sufferer due to uncertainty about the future, worry, fear, and making negative predictions. The present research aimed to describe the characteristics of working memory in a person with generalized anxiety disorder from a single case study. A sample of a single 21-year-old individual who met the diagnostic criteria for generalized anxiety disorder was used, and the Weshler Adults Intelligence Scale (WAIS-IV) was also used, taking into account only the subtests for the Working Memory Index (WMI). Regarding the results, the performance of the evaluated is located in the average range with no evidence of alterations in working memory, unlike other antecedents that studied this variable in the same disorder.
Keywords: Trastorno de ansiedad generalizada; Memoria de trabajo; Funciones ejecutivas; a